Sarah the Sunday fairy - Meadows, Daisy (New York : Scholastic, 2008)
There's a flag missing and it belongs to Sarah the Sunday Fairy. Rachel and Kirsty will do anything to get it back, but so will Jack Frost.
Rainbow magic: The fun day fairies ;v07.
Rainbow magic ;42.
Ages 6-9.
Accelerated Reader/Renaissance Learning
Keywords: Tate, Kirsty (Fictitious character) -- Juvenile fiction; Walker, Rachel (Fictitious character) -- Juvenile fiction; Jack Frost (Legendary character) -- Juvenile fiction; Fairies -- Juvenile fiction; Flags -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction, Juvenile